PENGARUH RASIO PROFITABILITAS, LEVERAGE DAN ACTIVITY TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR - FAISAL RUSLI, IVAN (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:This research aims to analyzed the influence of profitability, leverage, and activity ratio to the stock return manufacturing companies in Indonesia Stock Exchange (IDX) on period 2008-2012.The independent variables in this research consisted of profitability, leverage, and activity ratio. Profitability measured by Return On Equity (ROE) and Return On Asset (ROA), leverage measured by Debt to Equity Ratio (DER), and activity ratio measured by Earning Per Share (EPS) and Price Earning Ratio (PER). The number of sample used in this reseach consisted of 12 companies on sub sector food and beverages listedon IDX taken by a purposive sampling method. Research finding indicates thatROE, ROA,DER andEPS do not have effect to stock return. OnlyPERhas positive and significant influence to stock return. Keywords: profitability, leverage, activity and stock return.